BIOSORPTION OF Cd(II) ION BY DRAGON FRUIT PEEL (Hylocereus polyrhizus) - Tanasal A.M; Nursiah La Nafie; Paulina Taba (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2015)
Abstract. Dragon fruit peel is a material that is abundant and cheap. The material has been used as an adsorbent in the biosorption process for the removal of metal ions of Cd(II) from wastewater. Biosorption of Cd(II) ion by dragon fruit peel was done on the variation of contact time, pH and concentration. The concentration of metal ions Cd(II) before and after adsorption was determined using Atomic Absorption Spectrophotometer (AAS). Results showed that the optimum time was 20 minutes and the optimum pH was 5. Adsorption capacity was studied by both isotherm adsorptions of Langmuir and Freundlich. Results showed that the biosorption of Cd(II) ion using dragon fruit peel full filled the isotherm Langmuir model with the biosorption capacity (Qo) of 36,50 mg/g. The functional group involved in metal ion biosorption of Cd(II) by the peel of dragon fruit is a hydroxyl group (-OH).